Analysis of Radionuclide Deposition Ratios from the Fukushima-Daiichi Incident. Issue 1 (January 2018) - Marianno, C.M.; Smith, M.R.; Cook, K.M.
Abstract : Abstract: This paper will examine deposition patterns of four radionuclides following the Fukushima-Daiichi accident. For nearly 13 d following the event, fission products were released into the environment through planned venting procedures and hydrogen explosions. To assist the government of Japan (GOJ) in the assessment of the releases, the National Nuclear Security Administration's Consequence Management Response Team (CMRT) deployed and took nearly 3 mo of measurements using airborne radiation sensors, fixed monitors, high purity germanium (HPGe) detectors, and health physics survey equipment. From the HPGe detector in-situ results gathered by the CMRT and GOJ teams, the depositions of 134 Cs, 136 Cs, 137 Cs, and 131 I were examined as a function of latitude and longitude. Deposition ratios were calculated to express how each radionuclide was deposited relative to 137 Cs. In addition, the first 30 d of results were compared to the isotopic ratios listed in the Federal Radiological Monitoring and Assessment Center (FRMAC) Dose Assessment Manual Volume 2 Nuclear Power Plant default scenario. This was completed to analyze how the default FRMAC values compared with actual measurements. For 134 Cs: 137 Cs and 136 Cs: 137 Cs (1 wk after shutdown), the ratios were 0.969 ± 0.025 and 0.13 ± 0.007, respectively. These were significantly different from the FRMAC default values of 1.6 and 0.4, but they were of the same order of magnitude. Spatially, larger ratios with high uncertainties were recorded near Tokyo, over 200 km from the accident site. The 131 I to 137 Cs ratios, as expected, decayed exponentially over time but were significantly higher than FRMAC values. Six ratios were greater than 20 within 10 d after shutdown compared to the FRMAC default value of 9.9. In addition, the highest ratios were located less than 75 km to the southwest of the plant. Comparing all the isotopic ratios to the FRMAC manual illustrated differences between the default values and the actual field results. This is at least partly due to the fact that the FRMAC default values are based on an average between a pressurized water reactor and boiling water reactor release. These results of the comparison illustrate that the Assessment Manual default values should only be used when no other data are available.